Head Injury Simulation in Road Traffic Accidents - Fernandes, Fábio A. O. (SpringerBriefs in Applied Sciences and Technology,, 2018)
In this work the development of a new geometrically detailed finite element head model is presented. Special attention is given to sulci and gyri modelling, making this model more geometrically accurate than others currently available. The model was validated against experimental data from impact tests on cadavers, specifically intracranial pressure and brain motion. Its potential is shown in an accident reconstruction case with injury evaluation by effectively combining multibody kinematics and finite element methodology. .